Si ge yuan wang - Shih, Yi-Hsin (Hui ben guan, 2014)
"A long time ago, at the foot of No Sorrow Mountain lived Ajun and his mother. They both worked very hard for a living but were still very poor. Ajun heard that on an island in the south, lived a very wise man. So he decided to go and ask him why he worked so hard and still poor? ..."--Provided by vendor